(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Globalization has a large global role to play. In every area of life it has left its footprints behind. In India alone, but also via the exchange of global perspectives and ideas, the way people live and live worldwide has changed. This process of change is not hindered by Indian culture. The rise of globalisation has loosened our deep-rooted traditions and habits. India has a rich cultural history and is renowned all over the globe for its culture. Not only did globalisation instill Westernization in India, but the Indian culture has internationally expanded its influence. A particular importance is attached to the culture and customs of every geographical area, which distinguish a people within a geographic limit from another. Instead of globalisation, this particular feature is disrupted to different degrees. Such an effect is evident when it hits a developing nation such as India.